Konsumpcja towarów z Unii Europejskiej na Ukrainie - Butyter, Daniel (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
The World economic crisis had a signifi cant impact on the economic relations of Ukraine and EU countries, changing the structure of trade in goods and services. Despite the crisis, negotiations between the UE and Ukraine on setting the Association Agreement, new twining and technical assistance projects were launched, cooperation was active in the energy sector etc. Financial crisis led to a decrease in the volume and flow of FDI from EU, although the presence of European bans in the country facilitated entry of more capital, than it would have been otherwise, as these banks actively re-capitalized Ukrainian daughter institutions. Ukraine remains a very important market for Europe, but still there is much to be done to improveeconomic development and relations.
Keywords: Ukraina; konsumpcja; Unia Europejska; towary